Effect of hyperinsulinemia and very-low-calorie diet on interstitial cytokine levels in subcutaneous adipose tissue of obese women - Siklova-Vitkova, Michaela; Polak, Jan; Klimcakova, Eva; Vrzalova, Jindra; Hejnova, Jindra; Kovacikova, Michaela; Kovacova, Zuzana; Bajzova, Magda; Rossmeislova, Lenka; Hnevkovska, Zuzana; Langin, Dominique; Stich, Vladimir (American journal of physiology. Endocrinology and metabolism, 2009)
Type 2 diabetes and obesity are associated with an enhanced release of a number of adipocytokines. Hyperinsulinemia, frequently present in type 2 diabetes and obesity, might be one of the drivers of the enhanced production of adipocytokines. The aim of this study was to investigate the interstitial levels of cytokines in subcutaneous adipose tissue (SCAT) in response to hyperinsulinemia and the effect of weight-reducing hypocaloric diet on this regulation in obese subjects. Thirteen obese premenopausal women participated in the study. Concentrations of seven cytokines were measured in plasma and in AT interstitial fluid collected by microdialysis during a euglycemic-hyperinsulinemic clamp and during control infusion of physiological saline. A subgroup of six women underwent a 4-wk very-low-calorie diet (VLCD). Microdialysis during the clamp was performed before and at the end of VLCD. Hyperinsulinemia induced an increase of monocyte chemoatractant protein (MCP-1) and IL-6 SCAT interstitial and plasma levels and elevated IL-8 levels in SCAT. The relative changes of IL-6 levels in the dialysate correlated with changes of IL-8 and MCP-1. The interstitial and plasma levels of IL-1β, IL-10, TNFα, and plasminogen activator inhibitor (PAI-1) remained unchanged in response to hyperinsulinemia. VLCD resulted in enhancement of the hyperinsulinemia-induced augmentation of MCP-1, IL-6, and IL-8 interstitial levels. In conclusion, hyperinsulinemia upregulates the interstitial levels of MCP-1, IL-6, and IL-8 in SCAT in obese women, whereas it does not affect IL-1β, IL-10, TNFα, and PAI-1 levels. Hypocaloric diet associated with weight reduction enhances the hyperinsulinemia-induced upregulation of MCP-1, IL-6, and IL-8 in SCAT.
Keywords: dospělí; homeostáza; Hyperinsulinism; Caloric Restriction; Female; Cytokines; Interleukin-8; Adult; ženské pohlaví; Obesity; cytokiny; Chemokines; lidé; podkožní tuk; Homeostasis; Subcutaneous Fat; Interleukin-6; Microdialysis; glykemický clamp; mikrodialýza; Middle Aged; interleukin-8; hyperinzulinismus; chemokin CCL2; obezita; Chemokine CCL2; Insulin Resistance; interleukin-6; inzulinová rezistence; chemokiny; lidé středního věku; Glucose Clamp Technique; kalorická restrikce; Humans